Persons in Context. A Model to Represent Observations and Reconstructions of Historical Persons in Linked Data - Pieter E. Woltjer; Ivo Zandhuis; Bob Coret; Mark Lindeman; Jeroen D. Balkenende; Richard L. Zijdeman; Rick J. Mourits (Historical Life Course Studies)
Reconstruction of historical persons and family ties is the bread and butter of many researchers and genealogists. With the increasing digital availability of historical person records, the scope and depth of person reconstructions speaks to the imagination of researchers and genealogists. Yet, the lack of standardisation in the description of historical person data has hurt the interoperability and sustainability of both small and large databases. Persons in Context, or PiCo, presents a data model for historical person records within the Resource Description Framework (RDF). RDF or Linked Data is specifically designed for clear, unambiguous information exchange between multiple parties over the internet. We show how reuse of existing ontologies and concentric description are the building blocks of a flexible, straightforward, and stringent data model that emphasises provenance.